POLA PENANAMAN NILAI AGAMIS ANAK DALAM PENCEGAHAN TINDAKAN KRIMINALITAS BERBASIS BISA (BERIMAN, INTELEKTUAL, SEHAT DAN AKTIF): (Studi Pengabdian Pada Anak-anak Desa Johorejo Kecamatan Gemuh Kabupaten Kendal) - Ananda Alfikro; Bagas Putratama; Hamid Reza Asefi; Mohammad Ferdian Hastomo; Nurul Fitriah; Apriliana Drestisianti (Lembaga Pengembangan Kinerja Dosen, 2024)
Crime is a growing social problem that needs to be addressed seriously. One way to prevent crime is through religious education. Religious education plays an important role in shaping personal character based on moral and ethical values, thus preventing deviant behavior early on. This study aims to explore an effective religious education model in instilling moral and spiritual values as a preventive effort against criminal behavior. The research method used is a qualitative approach that combines documentary analysis and case studies of religious education institutions in Johorejo Village, Gemuh District, Kendal Regency. The findings show that structured and consistent religious education, which internalizes values such as honesty, responsibility, and tolerance, is very helpful in reducing the tendency of criminal behavior. In addition, the active participation of families and communities in the religious education process is an important factor in strengthening these values. Therefore, the development of a comprehensive and sustainable religious education model is an effective strategy to prevent social crime..